Determining the Effect of Natural Antibiotics on Selected Clinical Isolates from Minna General Hospital, Niger State, Nigeria - Bako, Erena Nuhu (Pharmaceutical Research - Recent Advances and Trends Vol. 2, 2024)
The present study highlights the effect of Redeemer's Natural antibiotics on selected clinical isolates from Minna General Hospital, Niger State, Nigeria. The knowledge of herbal medicine has grown. In modern times, a wide range of herbs have been sought for their healing effects and are used more and more, while the resort to black magic has been in steady decline. The antimicrobial activity of Redeemer’s Natural antibiotic was tested against five clinical isolates from Minna General Hospital, Niger State (Salmonella typhi, Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Candida albicans), using tube dilution techniques. It was found that Salmonella typhi was markedly affected by the herbal drug at a concentration of 2mg/ml, while Pseudomonas aeruginosa and Escherichia coli were also affected at a concentration of 3mg/ml, all three organisms were inhibited with a zone of inhibition ranging from 5.0mm-14.0mm, while the herbal drug showed no effect on Staphylococcus aureus and Candida albicans. The study further stated that the ethanol leaf and root extract of aloe vera gel has the intended effect of antibacterial activity against both Gram-positive and as well as Gram-negative bacteria. This investigation further assures that the plant extracts could be used for the treatment of microbial infections. The inactivity of the herbal drug on Staphylococcus aureus and Candida albicans can be due to drug resistance development. There is a promising future for “Redeemer’s Natural Antibiotic” as there are about half a million plants around the world, and most of them are not investigated yet for their medical activities and their hidden potential medical activities could be decisive in the treatment of present and future studies.